answersLogoWhite

0


Best Answer

Presumably you want to know the value of x 2x + 3 = 9x 3 = 9x - 2x 3 = 7x 3/7 = x So x = 3/7

User Avatar

Wiki User

โˆ™ 2009-08-15 14:11:40
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: 2X plus 3 equals 9 X?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

2x plus 3 equals 9 x equals?

2x+3=9 2x=9-3 2x=6 2x/2=6/2 X=3


What is 2x plus 3 equals 9?

if 2x+3=9 then 2x=6 so x=3


2x plus 3 equals 9 what is x equal?

2x + 3 = 9 2x = 6 x = 3


Solve 2x plus 3 equals 9?

3


2x plus 3 equals 9?

x=3.


How do you factor 4x2 plus 12x plus 9 equals 0?

(2x + 3)(2x + 3)


2x plus 3 equals -9?

2x + 3 = -92x = -12x = -6


What is 4x plus 3 equals 2x plus 9?

x=3


Y equals 5x plus 18 y equals 2x plus 9?

5x+18 = 2x+9 5x-2x = 9-18 3x = -9 x = -3 and y = 3


What is 2x plus 3 equals 9 what does x equal?

2x + 3 = 92x = 9 - 32x = 6x = 6/2x = 3


3x-3 equals 2x plus 6?

3x - 3 = 2x + 6 3x = 2x + 9 x = 9


What is the answer to the equation 2x plus 3 equals 9 x equals?

21


2x - 3 equals 4x plus 9?

2x-3=4x+9 -2x-12=0 2x=-12 x=-6


What is the answer for x plus 9 plus 5x equals 21 plus 2x?

If: x+9+5x = 21+2x Then: x = 3


How do you solve 2x-y equals -6 and 2x plus 3y equals 9?

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9


2x plus 9 equals 6x - 3?

2x+9=6x-3 Therefore 4x=12 -->x=3


2x plus 6y equals 24 and 5x - 2y equals 9?

(3, 3)


What is 6 plus 2x equals 5x plus 9?

6 + 2x = 5x + 9 , 6 - 9 = 5x - 2x , -3 = 3x , x = -1


Solve 2x plus 3 equals 9 x equals?

2x+3 = 9x 3 = 9x-2x = 7x 7x = 3 x = 3/7


2X-6 equals X plus 3?

X = 9


What are the order pairs for x equals y plus 3 and 2x plus y equals -3?

The answer is - not are - (-6, 9).


What is 2x plus 3 equals 9.x?

6 2(6) + 3 = 9


2x equals -x plus 9?

2x = -x +9


2X plus 3 equals 9 the X is?

2x+3=9 Your question is what is X value. 2x+3=9 2x=9-3 2x=6 2/2x=6/2 x=3 Best answer by Deo Math Club...


What is x in 2x plus 3 equals 9?

common it's very easy !!2x + 3 = 92x = 6x = 6/2x = 3